FORMATION OF YOUNGER PUPILS' SUSTAINABLE INTEREST TO TAKE PHYSICAL CULTURE IN OUTDOOR EDUCATION INSTITUTIONS - Bilavych, Halyna; Savchuk, Borys; Bilavych, Ivan; Pantiuk, Mykola; Khalo, Zoriana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The results of the study and the data of Ukrainian and foreign scientists showed that children are passively involved in physical activity. School lessons of physical culture lose their priority among the preferences of students. The interests of younger students in physical education contradict with the curriculum. Physical development has a declarative and situational nature, since only about 20% of children engage in motor activity in the morning. In view of this, the author developed a method of forming a sustainable interest in physical education and sports during the extracurricular institution, which has been introduced from 2017 to the present at the University of Gifted Child (UGC), which operates at the Vasyl Stefanyk Precarpathian National University (Ukraine). Here, they have created a special educational, development and leisure environment of health-conscious content. The study confirmed the hypothesis that the effectiveness of this process is provided by a number of conditions: students have knowledge of physical culture and sports, health, well-known fellow countrymen; practical activity of children; valuable attitude of younger students to physical education, motivation for healthy lifestyle, emotional satisfaction from exercise, physical activity, sports, active rest; highly professional teaching staff who are well-known athletes, creative students; innovative methods and forms of learning, etc. It is proved that if significant attention is paid to the cognitive and value components, then it is possible to generate more intense interest in physical culture in children